Increasing positive end-expiratory pressure (re-)improves intraoperative respiratory mechanics and lung ventilation after prone positioning. (19th May 2016) - Spaeth, J.; Daume, K.; Goebel, U.; Wirth, S.; Schumann, S.
Abstract : Background: Turning a patient prone, changes the respiratory mechanics and potentially the level of positive end-expiratory pressure (PEEP) that is necessary to prevent alveolar collapse. In this prospective clinical study we examined the impact of PEEP on the intratidal respiratory mechanics and regional lung aeration in the prone position. We hypothesized that a higher PEEP is required to maintain compliance and regional ventilation in the prone position. Methods: After ethical approval, 45 patients with healthy lungs undergoing lumbar spine surgery were examined in the supine position at PEEP 6 cm H2 O and in the prone position at PEEP (6, 9 and 12 cm H2 O). Dynamic compliance (CRS ) and intratidal compliance-volume curves were determined and regional ventilation was measured using electrical impedance tomography. The compliance-volume curves were classified to indicate intratidal derecruitment, overdistension, or neither. Results: CRS did not differ between postures and PEEP levels ( P >0.28). At a PEEP of 6 cm H2 O a compliance-volume profile indicating neither derecruitment nor overdistension was observed in 38 supine, but only in 20 prone positioned patients ( P <0.001). The latter increased to 33 and 37 (both P <0.001) when increasing PEEP to 9 and 12 cm H2 O, respectively. Increasing PEEP from 6 to 9 cm H2 O in the prone position increased peripheral ventilation significantly. Conclusions: Respiratory system mechanics change substantially between supine and prone posture, which is not demonstrated in routine measurements. The intratidal compliance analysis suggests that in most patients a PEEP above commonly used settings is necessary to avoid alveolar collapse in the prone position. Clinical trial registration: DRKS 00005692.